Planiglobii terrestris mappa universalis : utrumq hemisphærium orient. et occidentale repraesentans ex IV mappis generalibus Mappe-monde qui represente les deux hemispheres savoir celui de l'orient et celui de l'occident tireÌe des quatre cartes generales. - Hase, Johann Matthias, 1684-1742 (Homann Heritiers, 1746)
Map shows major cities and political divisions for eastern and western hemispheres; 5 continents and portions of the 6th [Australia]; islands south of the eastern tip of Asia and North American coastline extends further northwest in version of map described herein. Includes six ancillary maps: "Fig. I, Hemisphere polaire Arctique," "Fig. II, Hemisphere polaire Antarctiq," "Fig. III, Hemisphere de las Sphere oblique pour l'Horizon de Nuremberg," "Fig. IV, Les Antipodes de Nuremberg," and two additional figures showing the tilt of the earth at the summer and winter solstice. Relief shown pictorially. Scale not noted.